Chronic Lung Diseases and Pregnancy Outcomes in Saudi Arabia: A Narrative Review - Mudawi Ahmed, Einas Mustafa; Elrasheed, Fath Elrahman; Abdoon Osman, Yasser Hijazi; Rizig Omer, Asma Ali; Abuobidamohammed, Baharelden; Elmahboub Mohammed, Randah Abd Allah; Mohamedelhadi Abdelmajeed, Khalid; Hassan Al Gurini, Kholoud; Farah Obaid, Mayada (Journal of Neonatal Surgery, 2025)
Chronic lung diseases (CLDs), including asthma and chronic obstructive pulmonary disease (COPD), pose significant health challenges, particularly in pregnant women. This narrative review examines the prevalence of CLDs in Saudi Arabia, their impact on pregnancy outcomes, and management strategies. Key findings indicate that women with asthma are at an increased risk for preterm birth and low birth weight, while those with COPD may experience severe respiratory complications during pregnancy. The review highlights that approximately 30-40% of pregnant women with asthma may experience exacerbations, necessitating careful monitoring and individualized care. Cultural factors and socioeconomic barriers significantly influence healthcare access and management. Improved awareness and a multidisciplinary approach are essential for optimizing maternal and fetal health outcomes.